Overweight and obese adolescents: what turns them off physical activity? - Stankov Ivana; Olds Timothy; Cargo Margaret (BMC, 2012)
Abstract A systematic review of qualitative studies was undertaken to understand the barriers to physical activity experienced by adolescents who were overweight or obese. From a search of electronic databases and 'grey' literature, published between 1950 and 2009, 15 studies met the inclusion criteria. Bronfenbrenner's model of human development provided an ecological lens for identifying and synthesising barriers to physical activity. Two reviewers appraised study quality. Miles and Huberman's cross-case analysis was integrated with thematic networking to synthesize the individual, interpersonal and environmental level barriers for boys and girls of different ethnicities and socioeconomic status, across school settings and generalised context. Thirty-five barriers were identified, 13 of which occurred in physical activity situations in the school setting, 18 were not linked to a specific setting, and the remainder were common across both contexts. The fact that these barriers emerged from studies that focused on topics such as victimisation and mental health is particularly poignant and reflects the potentially pervasive influence of adolescent's excessive weight not only in relation to physical activity situations but other aspects of their lives. Furthermore, socioeconomic status and ethnicity was poorly considered, with only one study linking these participant characteristics to quotations and discussing the potential implications. At present, there are few qualitative studies with sufficiently thick description or interpretive validity that provide insight into this vulnerable group of adolescents, and give them a voice to influence policy and practice.